Effects of Carbonated Soft Drink on Saliva pH in the Occurrence of Dental Caries - Santoso, Theofany L. A.; Wicaksono, Dinar A.; Gunawan, Paulina N. (e-GiGi, 2022)
Abstract: One of the instantaneous lifestyle can be seen inter alia from the high level of soft drink consumption. Consumption of carbonated soft drinks produces a pH ranging from 2.4 to 4.07 which is classified as low. CO2 dissolved in carbonated soft drinks is thought to increase acidity, therefore, decrease the pH of saliva. The continuous decrease in salivary pH can lead to demineralization of tooth structure which triggers the occurrence of dental caries. This study aimed to determine the effect of soft drink consumption on salivary pH related to the incidence of dental caries. This was a literature review studi using four databases as follows: Google Scholar, PubMed, ScienceDirect, and ClinicalKey. The keywords were "minuman bersoda" OR "minuman berkarbonasi" AND "pH saliva"; dan â€œsoft drinkâ€ OR "carbonated drink" AND "salivary pH". The literatures were selected through inclusion and exclusion criteria and then a critical appraisal was carried out. The results showed that 29 abstracts met the criteria. Full-text articles that met the inclusion and exclusion criteria and be used in this study were 18 articles in total. It was found that there was a change in the degree of acidity after consuming carbonated drinks. In conclusion, carbonated soft drinks can affect the pH of saliva which triggers the occurrence of dental caries.Keywords: carbonated soft drinks; salivary pHÂ Â Abstrak: Salah satu gaya hidup masyarakat Indonesia yang serba instan dapat terlihat dari tingginya tingkat konsumsi minuman ringan bersoda. Minuman ringan ini tersedia secara komersil dan bila dikonsumsi menghasilkan pH berkisar antara 2,4 hingga 4,07 yang tergolong rendah. CO2 yang terlarut dalam minuman bersoda dianggap dapat meningkatkan keasaman dan menurunkan pH saliva. Penurunan pH saliva yang terjadi secara terus-menerus dapat menyebabkan demineralisasi struktur gigi yang merupakan awal dari terjadinya karies gigi. Penelitian ini bertujuan untuk mengetahui pengaruh konsumsi minuman bersoda terhadap pH saliva pada kejadian karies gigi. Jenis penelitian ialah suatu literature review, yang menggunakan database Google Scholar, PubMed, ScienceDirect, dan ClinicalKey serta kata kunci "minuman bersoda" OR "minuman berkarbonasi" AND "pH saliva"; dan â€œsoft drinkâ€ OR "carbonated drink" AND "salivary pH". Â Literatur diseleksi melalui kriteria inklusi dan eksklusi serta dilakukan critical appraisal. Hasil penelitian mendapatkan jumlah literatur sebanyak 29 abstrak yang memenuhi kriteria sedangkan artikel fulltext yang memenuhi kriteria inklusi dan eksklusi sebanyak 18 artikel. Hasil kajian mendapatkan terjadi perubahan derajat keasaman setelah mengonsumsi minuman ringan bersoda. Simpulan penelitian ini ialah minuman bersoda dapat memengaruhi pH saliva yang selanjutnya memicu terjadinya karies gigi.Kata kunci: minuman bersoda; pH saliva